Keabsahan Nikah Syigar Dan Mahar Mitsil Persepektif Imam Abu Hanifah - Darlius, Darlius (AL-MUTSLA, 2024)
This research is related to the thoughts of Imam Abu Hanifah who allows shigar marriages on the condition that both men must pay the mitsil dowry. This research seeks to reveal the reasons and legal guidelines used by Abu Hanifah regarding the permissibility of shigar marriage. This research method is library research which examines literature related to the research discussion, namely the books of al-Mabsuth and Badi'us Sana'i. Data were analyzed using descriptive analysis methods. Abu Hanifah is of the opinion that syighar marriage is prohibited because it makes the honor (budu') of the two women being married as a dowry, even though a woman's honor should not be used as a dowry, so that the dowry from the marriage becomes damaged (fasid), whereas "a marriage is not invalid just because the dowry is damaged (fasid)”, then in exchange for the damaged dowry (fasid) the two men are obliged to pay the mitsil dowry, this is required for marriages where the dowry is wine or pork. The prohibition in the two hadiths only shows that it is makruh, not haram, whereas "marriage is not invalidated by something that is makruh". The prohibition is also aimed at the essence of syighar, not at 'ain nikah. The argument that Abu Hanifah uses is a hadith narrated by 'Abdullah bin Umar "that the Prophet forbade marrying women without a dowry". The dowry is a right for the wife, not a guardian's right and an obligation for the husband, so a marriage cannot be empty or desolate from the dowry, as Allah SWT says in Surah an-Nisa: 4 and al-Baqarah: 236. In a broken syigar marriage (fasid ) is the dowry, not the contract, so that the marriage is not empty of dowry, in place of the damaged dowry (fasid) there is a mitsil dowry.